Experience With Rapid Microarray-Based Diagnostic Technology and Antimicrobial Stewardship for Patients With Gram-Positive Bacteremia. (8th August 2016) - Neuner, Elizabeth A.; Pallotta, Andrea M.; Lam, Simon W.; Stowe, David; Gordon, Steven M.; Procop, Gary W.; Richter, Sandra S.
Abstract : OBJECTIVE: To describe the impact of rapid diagnostic microarray technology and antimicrobial stewardship for patients with Gram-positive blood cultures. DESIGN: Retrospective pre-intervention/post-intervention study. SETTING: A 1, 200-bed academic medical center. PATIENTS: Inpatients with blood cultures positive for Staphylococcus aureus, Enterococcus faecalis, E. faecium, Streptococcus pneumoniae, S. pyogenes, S. agalactiae, S. anginosus, Streptococcus spp., and Listeria monocytogenes during the 6 months before and after implementation of Verigene Gram-positive blood culture microarray (BC-GP) with an antimicrobial stewardship intervention. METHODS: Before the intervention, no rapid diagnostic technology was used or antimicrobial stewardship intervention was undertaken, except for the use of peptide nucleic acid fluorescent in situ hybridization and MRSA agar to identify staphylococcal isolates. After the intervention, all Gram-positive blood cultures underwent BC-GP microarray and the antimicrobial stewardship intervention consisting of real-time notification and pharmacist review. RESULTS: In total, 513 patients with bacteremia were included in this study: 280 patients with S. aureus, 150 patients with enterococci, 82 patients with stretococci, and 1 patient with L. monocytogenes . The number of antimicrobial switches was similar in the pre–BC-GP (52%; 155 of 300) and post–BC-GP (50%; 107 of 213) periods. The time to antimicrobial switch was significantly shorter in the post–BC-GP group than in the pre–BC-GP group: 48±41 hours versus 75±46 hours, respectively ( P <.001). The most common antimicrobial switch was de-escalation and time to de-escalation, was significantly shorter in the post-BC-GP group than in the pre–BC-GP group: 53±41 hours versus 82±48 hours, respectively ( P <.001). There was no difference in mortality or hospital length of stay as a result of the intervention. CONCLUSIONS: The combination of a rapid microarray diagnostic test with an antimicrobial stewardship intervention improved time to antimicrobial switch, especially time to de-escalation to optimal therapy, in patients with Gram-positive blood cultures. Infect Control Hosp Epidemiol 2016;1–6